The California Nautical School - Dodson, Lieutenant Bennett M. (U.S. Naval Institute Proceedings)
Many officers of the fleet have seen the trim white training ship California State on the Pacific coast and in other parts of the world. It is not generally known that this ship is owned by the United States Navy, and that it is a part of the navy's program for the training of officers for vessels of the American Merchant Marine vessels that will form a definite source of supply to the fleet during war-time operations.